Preparation of Calcium Carbonate and Magnesium Oxide Nanoparticles by Co-Precipitation Technique - Jalil R. Ugal (Journal of Global Pharma Technology, 2018)
Calcium carbonate and magnesium oxide nano-particles were prepared by the co-precipitation method using their simple salts as starting materials. They were characterized by Atomic Force Microscope (AFM) and X-ray diffraction (XRD). The average diameter was 70 nm for CaCO3 and 84 nm for MgO nanoparticles. Keywords: Nan particles, AFM, X-ray diffraction.